ANALISIS KINERJA ORGANISASI PADA KANTOR PELAYANAN PERIZINAN TERPADU DAERAH PROVINSI SULAWESI TENGAH - Latang, Amelia (Katalogis, 2014)
The  objective  of  the  research  was  to  find  out  Organizational  Performance  in  RegionalIntegrated Licensing Service Official of Central Sulawesi Province. The used theory from Goggin and Joedono, Structure,Human Resourses, Financial, Tecnology and Leadership.The method employed in the research was qualitative with 5 informants chosen purposively as sample. The technique of data collection done through observation,interview and documentation. The research results revealed that the implementation organizational Performance of Regional Integrated Licencing  Service Official  of Central  Sulawesi Province have not  been  maximal  due to  some dimensions run unwell such as structural dimension not ideal; it still focused on license sector not to service fungcion. Whereas the recources dimension ; it still have double job and need discipline improvement to understand the duty and fungsion. The technology dimension; it wass already available but still not optimal due to the resourses limit. Financial dimension;basically it was already available but not used as the fungsion. Mereover, leadership dimension; it was always centered but not democratic. Based on the research result, there were some suggestions as solution for the problem namely;it needs to have a review  related to organizational structure to be more oriented to service function;;apparatus resourses have to change their mindset and paradigm, be more innovative,need to add the number of gualified apparatus  to avoid double job, conducting education of training for the unqualified tecnical staff with their main duty ,conducting foreign language cources to serve foreign investor,and be more democratic in conducting the leadership duty.